Persepsi Orang Tua Terhadap Guru dalam Upaya Mengoptimalkan Pengembangan Kepribadian Anak Usia Dini (Studi Kasus di Taman Kanak-Kanak Pertiwi Tanjungan, Wedi, Klaten) TahunAjaran 2015/2016 - Annisa, Auliya; , Dra.Surtikanti,S.H.,M.Pd (2016)
Singer study aims to review determine Perception Parents Against It self And hearts teacher Against Efforts to optimize Personality Development Children. Problems singer studied using qualitative descriptive approach case with Operations Research Studies . Execution time reseach In November 2015 until March 2016. Year hearts research data collection ethods interviews singer using, observation and documentation . The data obtained were analyzed with interactive analysis consisting of 4 steps that data collection , data reduction, data display, and withdrawal conclusion and verification . Furthermore, the data was analyzed in taxable income test its validity using the data model trianggulasi, trianggulasi methods and trianggulasi theory. Results showed that parents in kindergarten Pertiwi Tanjungan assume that keep the parents who have a fundamental obligation to form and optimize the development of the child personality . But parents realize that they must work to meet his family life . They looked to send their children to kindergarten Tanjungan Pertiwi, a teacher at the institute can help in optimizing the formation of the child's personality. In fact it is the teacher in kindergarten Pertiwi Tanjungan helped parents in shaping the personality of the child, the child began to enter until they come home . So parents in kindergarten Pertiwi Tanjungan already have the correct perception, both to themselves and to the teacher about optimization for the child 's personality development. This is consistent with the formation of good character in their children .